The Impact of Climate Variability on Yield and Export Volume in the South African Orange Industry - Kunene, Sanele; Hlongwane , Jan Johannes; Nengovhela, Rudzani (International Journal of Economics and Financial Issues, 2026)
Agriculture lies at the heart of South Africa’s economy, yet its performance is increasingly shaped by the unpredictable rhythm of the climate. Nowhere is this more evident than in the orange industry, a cornerstone of the nation’s agricultural exports and rural livelihoods. This study sought to examine how climatic fluctuations have impacted orange yield and export volumes between 2000 and 2021. Using annual time-series data from the World Bank and Trading Economics, the study applies descriptive statistics, the Augmented Dickey-Fuller (ADF) unit root test, and the Autoregressive Distributed Lag (ARDL) modelling framework to examine short-run and long-run relationships between temperature, precipitation, orange yield, and export volumes. The findings indicate that although climate variability has increased over the study period, its effect on orange yield is insignificant in both the short and long-run. However, a significant long-run relationship exists between orange yield and export volumes, emphasizing the dominant role of market dynamics in shaping production outcomes. This study contributes to the literature by distinguishing between climatic and market-driven influences on the industry’s production performance. The findings suggest that policy efforts should prioritize export infrastructure development, logistics efficiency, market access expansion, and continued investment in climate-resilient technologies to ensure long-term industry sustainability.